Legal Protection for Creditors Due to Criminal Acts of Embezzlement of Bankrupt Assets by Corporations - Asrul Azwar Siagian; Adi Mansar; Ida Nadirah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
Bankruptcy is a legal mechanism intended to ensure the fair and proportional distribution of a debtor's assets among its creditors in accordance with the principle of pari passu prorata parte. However, in practice, corporate debtors frequently commit the criminal act of embezzlement of bankruptcy assets by concealing, transferring, or reducing the value of assets that should form part of the bankruptcy estate. Such actions not only harm creditors as rightful beneficiaries but also undermine legal certainty and the effectiveness of bankruptcy law enforcement in Indonesia. This research aims to analyze the legal framework governing the criminal act of embezzlement of bankruptcy assets by corporations, examine the extent of legal certainty available to creditors, and formulate an ideal model of legal protection for creditors as victims. This study employs a normative juridical method with statutory, conceptual, and case approaches. The findings indicate a legal vacuum in procedural law concerning the criminal liability of corporations for inclusion of bankruptcy assets. Additionally, there exists regulatory disharmony between the Criminal Code, the Bankruptcy and PKPU Law, and Supreme Court Regulation (PERMA) No. 13 of 2016 regarding the prosecution of corporate crime. Therefore, legal reform is necessary through strengthened regulations, integration of criminal asset forfeiture into the bankruptcy estate process, and the consistent enforcement of corporate criminal liability doctrines to ensure effective legal protection for creditors.